The Effect of Classroom Management Ability and Teaching Style on the Teaching Readiness of Students of the Social Sciences Study Program of UIN North Sumatra Medan in the Micro Teaching Class for the 2023-2024 Academic Year - Ivan Prawita; Toni Nasution (Universitas Muhammadiyah Enrekang, 2024)
This study examines and analyzes the readiness of students in teaching, especially those who can manage classes and teach classroom social studies students for the 2023-2024 academic year at UIN North Sumatra Medan. This study focuses on the ability to manage courses, teaching styles, and readiness to teach students using quantitative research with an ex post facto approach. Data collection uses a questionnaire using the spss test version 2.2. This study uses two variables, namely classroom management (X1), teaching style (X2), and student teaching readiness (Y). The primary data used in this study is in the form of a questionnaire with 103 respondents. There was an influence between classroom management and teaching readiness because the t-value of the t-table > ( 7,994 > 1,984) and the significance level was 0.000 < 0.05. There was an influence between teaching style and teaching readiness because the t-value of the t-calculation > t table (9.224 > 1.984) and the significance level was 0.000 < 0.05. The simultaneity of Teaching Style and Classroom Management affects teaching readiness because of the value of f calculation > f table (27,635 > 3.09) and the significance level of 0.000 < 0.05.